Practical approach to improve growth and feed efficiency of Tor Soro fry by dietary supplementation of B-complex vitamins - Andri Hendriana; Aprida Anggraini; Yuni Puji Hastuti; Dudi Lesmana; Imam Tri Wahyudi (JURNAL MINA SAINS, 2026)
Tor soro is a freshwater fish species with high economic and ecological value. However, adequate production does not support the increasing demand for its fry, primarily due to its slow growth performance. One potential approach to overcome this limitation is feed enrichment with B-complex vitamins. This study aimed to evaluate the optimization of growth performance in T. soro fry through dietary supplementation of B-complex vitamins. The experiment was conducted using a Completely Randomized Design (CRD) with two treatments and three replicates: VT0 (0 g kg⁻¹) and VT1 (2 g kg⁻¹). Fish were reared for 60 days in aquaria (60 × 30 × 35 cm³). The results demonstrated that VT1 significantly improved (p < 0.05) both growth and feed performance. Absolute length and weight gain reached 2.85 ± 0.10 cm and 1.29 ± 0.03 g, while specific and daily growth rates were 3.96 ± 0.03% and 2.16 ± 0.05 g day⁻¹, respectively. Moreover, supplementation of B-complex vitamins reduced feed utilization, as indicated by feed conversion ratio (FCR) and feed efficiency values of 2.75 ± 0.06 and 36.43 ± 0.81%, respectively. These findings suggest that feed enrichment with B-complex vitamins can effectively enhance the growth performance of T. soro fry.